Effect of Fractionation on the Antifungal Activity of Peronema canescens Jack Extract Against Candida albicans on Acrylic Resin: Effect of Fractionation on the Antifungal Activity of Peronema canescens Jack - Okmes Fadriyanti; Edrizal Edrizal; Paridatul Ulya (Universitas Syiah Kuala, 2025)
Acrylic resin possesses surface porosity and rigidity, which can directly facilitate the adhesion of Candida albicans, a primary cause of denture stomatitis. While this condition can be prevented with common disinfectant solutions such as sodium hypochlorite, their use may cause surface damage to the acrylic resin. Sungkai leaves, containing secondary metabolites, offer an alternative as an antifungal agent. To determine the effect and differences in the fractionation of sungkai leaf (P. canescens Jack) as an antifungal on the quantity of C. albicans on heat-polymerized acrylic resin. The study samples consisted of 25 heat-polymerized acrylic resin plates measuring 10x10x1 mm, divided into five groups: sungkai leaf extract fractions using ethanol, ethyl acetate, and n-hexane solvents, along with positive and negative control groups. The research stages included fractionation of the sungkai leaf, fabrication of acrylic resin plates, and antifungal activity testing using a spectrophotometer. The results indicated that the lowest growth rate of C. albicans on heat-polymerized acrylic resin was observed in the n-Hexane fraction group (0.014 nm), compared with the positive control group (0.086 nm). The fractionation of sungkai leaf (P. canescens Jack) as an antifungal on heat-polymerized acrylic resin plates influences the quantity of C. albicans, with the most effective solvent being 1% n-Hexane.